Association of TCF7L2 genetic variants rs12255372 and rs7903146 with the polycystic ovary syndrome risk: systematic review and meta-analysis - Idrees A. Shah; Rabiya Rashid; Haroon Rashid; Abid Bhat; Mohd Ashraf Ganie (Journal of Ovarian Research)
Abstract Background A significant overlap in the pathophysiological features of polycystic ovary syndrome (PCOS) and type 2 diabetes mellitus (T2DM) has been reported; and insulin resistance is considered a central driver in both. The expression and hepatic clearance of insulin and subsequent glucose homeostasis are mediated by TCF7L2 via Wnt signaling. Studies have persistently associated TCF7L2 genetic variations with T2DM, however, its results on PCOS are sparse and inconsistent. Methods We performed a comprehensive literature review of the data published till June 2024, on rs7903146, rs12255372, and PCOS in PubMed, Medline, the Cochrane Library, Google Scholar, Science Direct, Scopus, and Web of Science, followed by a meta-analysis to evaluate the association between these genetic variations and the PCOS risk. Using a random effects model, the pooled odds ratio (OR) and confidence intervals (95%CI) were computed using STATA statistical software. Results The genotypic data from 3052 controls and 2291 women with PCOS from ten published studies were analysed. The results indicated no cumulative association between the rs7903146 variant and PCOS risk in either the allelic (C vs. T: OR = 1.21; 95% CI: 0.96–1.47, p > 0.05) or genotypic models (CC vs. CT + TT: OR = 1.06; 95% CI: 0.90–1.23, p > 0.05). Similarly, the genetic variant rs12255372 was not associated with PCOS risk both in the allelic and the dominant inheritance model(p > 0.05). Unlike East Asians (MAF < 0.025), both variants are highly frequent across other global populations including America, South Asia, and Europe (MAF ≥ 0.19). Conclusion Unlike T2DM, our results showed that rs7903146 and rs12255372 variants of the TCF7L2 gene do not modulate the PCOS risk. However, the role of other TCF7L2 variants remains to be studied in future studies.